Outcome and characteristics of invasive fungal infections in critically ill burn patients: A multicenter retrospective study. Issue 6 (10th May 2020) - Maurel, Véronique; Denis, Blandine; Camby, Matthieu; Jeanne, Mathieu; Cornesse, Aline; Glavnik, Boris; Alanio, Alexandre; Rousseau, Anne‐Françoise; Lefloch, Ronan; Lagrange‐Xelot, Marie; Textoris, Julien; Wiramus, Sandrine; et al.
Summary: Background: Characteristics and outcome of invasive fungal infection (IFI) in critically ill burn patients have been poorly explored. Objectives: We report the factors associated with 90‐day mortality in a multicentre retrospective European study. Patients/Methods: All burn patients with confirmed IFI admitted between 1 January 2010 to 31 December 2015 in 10 centres in France and Belgium were included. Results: Ninety‐four patients were enrolled with 110 cases of IFIs: 79 (71.8%) were yeasts IFI and 31 (28.2%) filamentous IFI. Incidence was 1% among admitted patients. The 90‐day mortality was 37.2% for all IFIs combined, 52% for filamentous infection and 31.9% for yeast infection. Patients with more than one IFI had a higher 90‐day mortality than patients with only one episode (61.5% vs 33.5% ( P = .006)). In multivariate analysis, higher Simplified Acute Physiology Score II (OR = 1.05 (95% CI: 1.02‐1.09) P = .003), bacterial co‐infection (OR = 3.85 (95% CI: 1.23‐12.01), P = .014) and use of skin allografts at the time of IFI diagnosis (OR = 3.87 (95% CI: 1.31‐11.42), P = .021) were associated with 90‐day mortality. Conclusions: Although rare, invasive fungal infections remain associated with poor outcome in burn patients. Bacterial co‐infection and presence of allograft were potentially modifiable factors independently associated with outcome.